exo-FISH: protocol for detecting DNA breaks in repetitive regions of mammalian genomes - Saayman, X; Graham, E; Leung, CWB; Esashi, F (Cell Press, 2023)
Detecting DNA breaks in defined regions of the genome is critical to advancing our understanding of genome stability maintenance. Here, we present exo-FISH, a protocol to label exposed single-stranded DNA in defined repetitive regions of mammalian genomes by combining in vitro restriction enzyme digestion on fixed cells with fluorescence in situ hybridization (FISH). We describe steps for cell harvesting and fixation, slide treatments, and FISH probe hybridization. We then detail procedures for imaging and analysis.